Methaemoglobinemia in nitrobenzene poisoning. - Chongtham D (Journal of Postgraduate Medicine, 1997)
A young girl with nitrobenzene induced methaemoglobinaemia was saved by the timely use of mechanical ventilator, administration of oral methylene blue and parenteral ascorbic acid. Though parenteral methylene blue is the antidote of choice, due to its non-availability, the laboratory preparation of methylene blue have been utilized orally. The rare occurrence of such cases, and the efficacy of oral methylene blue and other supportive measures in evading death due to Nitrobenzene poisoning have been highlighted.